Magnetic ordering and charge transport in electron-doped La₁-yCeyMnO₃ (0.1 ≤ y ≤ 0.3) films - Prokhorov, V.G.; Kaminsky, G.G.; Flis, V.S.; Hyun, Y.H.; Park, S.Y.; Lee, Y.P.; Svetchnikov, V.L. (Физика низких температур, 2009)
Microstructure, magnetic and transport properties of the as-deposited La₁−yCeyMnO₃(0.1 ≤ y ≤ 0.3) films, prepared by a pulse laser deposition, have been investigated in wide region of temperature and magnetic field. The microstructure analysis reveals that all films have a high c-oriented texture, the orthorhombic crystal lattice and the negligible quantity of CeO₂ inclusions. The observed strip-domain phase with a periodic spacing of about 3c, the crystal lattice of which is the same to the basic film phase, reveals the magnetic behavior typical for the Griffiths phase. The regions of the double-period modulated phase was found at room temperature in the y = 0.1 film, which are treated as the Mn³⁺/Mn²⁺ ordering with the partial ferromagnetic → antiferromagnetic transition at TN ≤ 80 K. At the same time, the carried out investigation manifests that the magnetic and transport properties of the electron-doped La₁-yCeyMnO₃ films, driven by a cation doping, are similar to that for the hole-doped La/Ca manganites. Therefore, one can conclude, that does not exist of a principle difference between the mechanisms of spin-ordering and charge-transport in the hole- and the electron-doped manganites.